Childfree Men: The Reasons Behind the Decision - Michelle Yonathan; Intan Primadini (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2023)
Childfree is a phenomenon that has been popular since the 1970s and is becoming more common in a number of nations, including Asia. Childfree has recently gained popularity among Indonesians. As a patriarchal culture, the majority of Indonesians subscribe to pro-natalism, making childfree a taboo subject to discuss or even make a choice. Surprisingly, when stated by women, the decision to be childless is highly condemned by society. Meanwhile, when males express their intention to be childless, society tends to laud individuals involved. As a result, the researcher hopes to learn more about the factors that influence men's decisions to be childless in Indonesia through this research. As a data collection strategy, this study used an exploratory qualitative approach, employing interpretive phenomenology methodologies, and conducting interviews with four individuals. The findings revealed being childfree was selected based on both internal and environmental influences. The experiences of participants in choosing childfree marriage can then be viewed via symbolic interactionism theory by Herbert Blumer.